MATHEMATICAL APPLICATION OF REVISED SIMPLEX MODELLING IN OPTIMAL LOAN PORTFOLIO - Kusi, Prince; Darteh, Andrews Ohene; Teku, Emmanuel; Acheampong, Samuel (Journal of Statistics and Actuarial Research, 2019)
Purpose: The main aim of this study is to develop Linear Programming (LP) model to help ADB, Sunyani branch in the Brong Ahafo Region to allocate their funds to prospective loan seekers in order to maximize profits. Methodology: To achieve this aim, a secondary data were extracted from the annual reports and financial statements of the bank. Based on these empirical data, LP model was formulated. A computerized software application called LP Solver based on Revised Simplex Algorithm was used to solve the problem. Results: The results from the model showed that ADB, Sunyani branch would be making annual profit of GH¢ 476732.00 on loans alone as against GH¢ 190693.00 in 2011 if they stick to the model. Unique contribution to Theory, Practice and Policy: From the study, it was realized that the Scientific method used to develop the proposed model can have a significant increase in the Bank's profit margin if put into use.